Commercial whey products promote intestinal barrier function with glycomacropeptide enhanced activity in downregulating bacterial endotoxin lipopolysaccharides (LPS)-induced inflammation in vitro. Issue 7 (7th July 2020) - Arbizu, Shirley; Chew, Boon; Mertens-Talcott, Susanne U.; Noratto, Giuliana
Abstract : Commercial whey products promote healthy gut by upregulating barrier function related molecules with glycomacropeptide (GMP) having enhanced activity in protecting colon cells against inflammation. Abstract : Cheese whey contains bioactive compounds which have shown multiple health-promoting benefits. This study aimed to assess the commercial whey products (CWP) whey protein isolate (WPI), galacto-oligosaccharide-whey protein concentrate (GOS-W) and glycomacropeptide (GMP) for their potential to improve intestinal health in vitro using HT29-MTX intestinal goblet and Caco-2 epithelial cells. Results from HT29-MTX culture showed that WPI mitigated reactive oxygen species (ROS) production at a higher extent compared to GOS-W or GMP. However, GMP downregulated the lipopolysaccharide (LPS)-induced TLR-4 inflammatory pathway with the highest potency compared to the other CWP. Biomarkers of epithelial integrity assessed on both cell lines showed tight junction proteins claudin-1, claudin-3, occludin (OCC), and zonula occludens-1 (ZO-1) upregulation by GMP in HT29-MTX (1.33–1.93-fold of control) and in Caco-2 cells (1.56–2.09-fold of control). All CWP increased transepithelial electrical resistance (TEER) in TNF-α challenged Caco-2/HT29-MTX co-culture monolayer ( p < 0.05), but only GMP was similar to the positive control TGF-β1, known for its role in promoting epithelial barrier function. The TNF-α-induced co-culture monolayer permeability was prevented at similar levels by all CWP ( p < 0.05). In conclusion, CWP may be used as functional food ingredients to protect against intestinal disorders with emphasis on the GMP enhanced anti-inflammatory and intestinal barrier function properties. Further in vivo studies are guaranteed to validate these findings.